Determinants of vaccination coverage during the COVID-19 pandemic among children aged 12–23 months in southern Ethiopia: a cross-sectional study - Gedamu, Tigist Enyew; Assemie, Anmut; Aleye, Leyla Temam; Woldemariam, Meskerem Teketel; Argago, Tsegaye Gebre; Buda, Alula Seyum (Frontiers in Pediatrics, 2025)
BackgroundMillions of children, particularly in low and middle-income countries, are deprived of a comprehensive vaccination schedule. The advent of the COVID-19 pandemic exacerbated this issue by significantly disrupting vaccination schedules and other critical health initiatives. In light of this challenge, our study sought to evaluate vaccination coverage and identify its determinants among children aged 12–23 months in southern Ethiopia during the COVID-19 pandemic.MethodsWe conducted a community-based cross-sectional study. Three kebeles were purposively selected, with 415 households with 12–23-month-old children from each kebele selected using a systematic sampling technique. Data were collected using an adapted Ethiopian 2019 Mini Demographic Health Survey immunization coverage tool. Data were entered, cleaned, and checked using EpiData version 3.1 and analyzed using SPSS version 24. Bivariate and multivariable logistic regression analyses were performed. Variables with a P-value of <0.05 were considered significant determinants of full vaccination coverage.ResultsOur study found that the full vaccination coverage rate among children in the study area was 44.5% (95% CI = 39.8–49.4). Households with two children were nearly twofold more likely to be fully vaccinated (AOR = 1.99, 95% CI = 1.01–3.95, P-value = 0.047), children whose caregivers reported traveling to the nearest immunization site were nearly threefold more likely to be fully vaccinated (AOR = 2.78, 95% CI = 1.38–5.57, P-value = 0.004,), children who underwent multiple immunization schedules were less likely to be fully vaccinated (AOR = 0.068, 95% CI = 0.035–0.134, P-value = 0.000), and children whose caregivers reported receiving information from television were twice as likely to be fully vaccinated (AOR = 2.02, 95% CI: 1.05–3.89).ConclusionsIn summary, our findings indicate a pressing need to address the identified determinants to improve vaccination coverage, which is currently below the World Health Organization's recommended levels. Therefore, targeted efforts must be made to enhance awareness and accessibility, particularly focusing on family size, logistical barriers, multiple immunization schedules, and effective communication through various media channels. Meeting the recommended vaccination rate will require coordinated action among healthcare providers, policymakers, and communities.